Comparison of two different starting dose of rhFSH in GnRH antagonist protocol for patients with normal ovarian reserve - Jia, Zhi-cheng; Li, Yong-qian; Li, Ran; Hou, Sen; Xia, Qing-chang; Yang, Kai; Wang, Pei-xuan; Li, Shu-miao; Sun, Zhen-gao; Guo, Ying (Frontiers in Endocrinology, 2023)
Objective: To evaluate different starting doses of recombinant human follicle-stimulating hormone (rhFSH) on pregnancy outcomes for patients with normal ovarian reserve during gonadotropin-releasing hormone antagonist (GnRH-ant) protocol-controlled ovarian stimulation of in vitro fertilization (IVF) cycles. Methods: In this retrospective study, a total of 1138 patients undergoing IVF cycles following the GnRH-ant protocol were enrolled. Patients were divided into two groups according to the starting dose of rhFSH. 617 patients received a starting dose of rhFSH of 150 IU, and 521 patients received a starting dose of rhFSH of 225 IU. We compared demographic characteristics, ovarian stimulation and embryological characteristics, and pregnancy and birth outcomes between the two groups. Multivariate logistic regression analysis was performed to examine the possible effects of the known potential confounding factors on pregnancy outcomes. Results: The number of oocytes retrieved in the 150 IU rhFSH group was significantly lower than those in the 225 IU rhFSH group. There was no significant difference between the two groups referring to embryological characteristics. The proportion of fresh embryo transfer in the 150 IU rhFSH group was significantly higher than that in the 225 IU rhFSH group (48.30% vs. 40.90%), and there was no difference in the risk of ovarian hyperstimulation syndrome and pregnancy outcomes between the two groups. Conclusions: In conclusion, the starting dose of rhFSH of 150 IU for ovarian stimulation has a similar pregnancy outcome as starting dose of rhFSH of 225 IU in GnRH-ant protocol for patients with normal ovarian reserve. Considering the potential cost-effectiveness and shorter time to live birth, the starting dose of rhFSH of 150 IU may be more suitable than 225 IU.